Analisis Tata Kelola dan Pengawasan Keuangan Sekolah di SMA Bukit Asam Tanjung Enim - Dahyani, Tenny (Yayasan Sembilan Pemuda Indonesia, 2021)
School institutions are concerned not only with education, but also with human resources and finances. The aim of this article is to learn more about how SMA Bukit Asam Tanjung Enim manages and supervises school finances. Data is gathered by exploration, questioning and answering, and file analysis. This analysis approach is a mix of techniques. The triangulation approach was used to interpret the qualitative data, and the quantitative data was statistically analyzed. Treasurers, deputy principals, students, and principals at SMA Bukit Asam Tanjung Enim were the study's target sources. The findings of this study show that school financial management and oversight in the implementation of the school budget work plan is acceptable and efficient. The preparation of the RAPBS or RKAS and accountability reports, which have been completed in compliance with the financial management framework and financial management principles, namely the principle of openness, the principle of accountability, and the principle of performance, demonstrate the management and monitoring of school finances, the principle of effectiveness, the principle of efficiency so that the management and supervision of school finances in SMA Bukit Asam is running well and the cooperation of the school and the community to advance the school is getting better.